2020
DOI: 10.1002/bjs5.50353
|View full text |Cite
|
Sign up to set email alerts
|

Shortening surgical training through robotics: randomized clinical trial of laparoscopic versus robotic surgical learning curves

Abstract: Background: Minimally invasive surgery is the standard technique for many operations. Laparoscopic training has a long learning curve. Robotic solutions may shorten the training pathway. The aim of this study was to compare laparoscopic with robotic training in surgical trainees and medical students. Methods: Surgical trainees (ST group) were randomized to receive 6 h of robotic or laparoscopic simulation training. They then performed three surgical tasks in cadaveric specimens. Medical students (MS group) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In conclusion, robotic liver resection can be safely established within a manageable period. This seems to be due to a shorter learning curve for robotic when compared to laparoscopic surgery [30,31]. Whether the robotic technique is generally superior to the laparoscopic technique cannot be concluded based on our data.…”
Section: Discussionmentioning
confidence: 74%
“…In conclusion, robotic liver resection can be safely established within a manageable period. This seems to be due to a shorter learning curve for robotic when compared to laparoscopic surgery [30,31]. Whether the robotic technique is generally superior to the laparoscopic technique cannot be concluded based on our data.…”
Section: Discussionmentioning
confidence: 74%
“…As discussed and increasingly evaluated in the literature, the learning curve of RAS and RAS experience play a significant role in its success and observed complication rates, as well as in relation to the operating time. Interestingly, a study of training time involving 42 participants found that less time was taken learning with RAS than with LA [ 55 ]. One robotic system, the Senhance ® surgical system, implements a new technology, referred to as haptic feedback [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the acquisition of surgical skills in a simulation setting takes less time with a robotic than with a laparoscopic platform. 112 Achieving technical proficiency has also been shown to take less time with robotic systems across an array of surgical procedures, including hepatectomies, colectomies and nephrectomies. [113][114][115] The faster acquisition of skills via robotic training is partly facilitated by high fidelity simulations available on the robotic consoles.…”
Section: Michal Kawka and Tamara Gallmentioning
confidence: 99%